Interferon-Gamma Release Assays Are a Better Tuberculosis Screening Test for Hemodialysis Patients: A Study and Review of the Literature. Issue 3 (2012) - Grant, J; Jastrzebski, J; Johnston, J; Stefanovic, A; Jastrabesky, J; Elwood, K; Roscoe, D; Balshaw, R; Bryce, E
Abstract : Diagnosing latent tuberculosis (TB) infection (LTBI) in dialysis patients is complicated by poor response to tuberculin skin testing (TST), but the role of interferon-gamma release assays (IGRAs) in the dialysis population remains uncertain. Seventy-nine patients were recruited to compare conventional diagnosis (CD) with the results of two IGRA tests in a dialysis unit. Combining TST, chest x-ray and screening questionnaire results (ie, CD) identified 24 patients as possible LTBI. IGRA testing identified 22 (QuantiFERON Gold IT, Cellestis, USA) and 23 (T-spot.TB, Oxford Immunotec, United Kingdom) LTBI patients. IGRA and CD correlated moderately (κ=0.59). IGRA results correlated with history of TB, TB contact and birth in an endemic country. TST was not helpful in identifying LTBI patients in this population. The tendency for IGRAs to correlate with risk factors for TB, active TB infection and history of TB argues for their superiority over TST in dialysis patients. There was no superiority of one IGRA test over another.